Over a million students use our free study notes to help them with their homework
The way to solve simultaneous equations is to 'slot in' one equation into the other. For this question, we will use the information in equation 2 (after manipulating it) to solve equation one. First, we a...
Let's think backwards - what can we multiply to get this result?First, let's take a simpler example, an expression:(x-1)(x-2). We multiply 1st term of the 1st brackets by terms of the 2nd bracket and then...
f(x) = x3 + 3x V = π ∫ (f(x)2) dx V = π ∫02 (x3 + 3x)(x3 + 3x) dx V = π ∫02 (x6 + 6x4Answered by Zac C. • Maths tutor2945 Views
Mary = 20km/h Jason = 15km/h s = d/t After 1.5 hours, Mary = 30km and Jason = 22.5km 30 + 22.5 = 52.5km
Factorising gives: y = (x+2)(x+1) = 0. y only equals 0 when (x+2)=0 or (x+1)=0. Therefore x=-2 or x=-1
←
677
678
679
680
681
→
Internet Safety
Payment Security
Cyber
Essentials